Neuroregenerative gene therapy to treat temporal lobe epilepsy in a rat model. (January 2022) - Zheng, Jiajun; Li, Tingjie; Qi, Shuang; Qin, Bing; Yu, Jiandong; Chen, Gong
Highlights: NeuroD1 converts hippocampal CA1 reactive astrocytes into GABAergic neurons in TLE rats. Neuroregenerative gene therapy rescues neuronal loss in epileptic hippocampus. Regeneration of GABAergic neurons reduces seizure activity and rescues behavioral abnormalities. Abstract: Temporal lobe epilepsy (TLE) is a common drug-resistant epilepsy associated with abundant cell death in the hippocampus. Here, we develop a novel gene therapy-mediated cell therapy that regenerates GABAergic neurons using internal hippocampal astrocytes to suppress seizure activity in a rat TLE model. We discovered that TLE-induced reactive astrocytes in the hippocampal CA1 region can be efficiently converted into GABAergic neurons after overexpressing a neural transcription factor NeuroD1. The astrocyte-converted neurons showed typical markers of GABAergic interneurons, fired action potentials, and formed functional synaptic connections with other neurons. Following NeuroD1-mediated astrocyte-to-neuron conversion, the number of hippocampal interneurons was significantly increased, and the spontaneous recurrent seizure (SRS) activity was significantly decreased. Moreover, NeuroD1 gene therapy treatment rescued total neuronal loss in the CA1 region and ameliorated the cognitive and mood dysfunctions in the TLE rat model. These results suggest that regeneration of GABAergic interneurons through gene therapy approach may provide a novel therapeutic intervention to treat drug-resistant TLE.